2003
DOI: 10.1021/ja0288690
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Magnetic Properties of the Fullerene-Based Ferromagnets Eu3C70 and Eu9C70

Abstract: Intercalation of C(70) with europium affords two kinds of magnetic compounds, a canted antiferromagnet Eu(x)C(70) (x approximately 3) and a ferromagnet Eu(x)C(70) (x approximately 9) with transition temperatures (T(C)) of 5 and 38 K, respectively. The Curie constants in the paramagnetic phase and the saturation moment in the ferromagnetic phase are both understood by the full moment of Eu(2+) for both systems. The structure of Eu(3)(-)(delta)C(70) (delta approximately 0.27) is pseudo-monoclinic, derived by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…A similar reversibility of the pressure-induced polymerization has also been reported in other intercalated fullerides. 18,[38][39][40] From another point of view the covalent 3D network in such C 60 polymers, containing carbon cages, can be seen as carbon analogs of silicon clathrate compounds. Recently, the barium-containing silicon clathrate compound Ba 8 Si 46 , isotypic with the type-I gas (G) hydrate Gx-(H 2 O) 46 , has been proved to be a superconductor with a transition temperature (T c ) of 8.0 K. 41 It could, therefore, be speculated that the 3D Na 4 C 60 phase observed in our experiments might possess a structure similar to that of such compounds but composed of carbon instead of silicon.…”
Section: Discussionmentioning
confidence: 99%
“…A similar reversibility of the pressure-induced polymerization has also been reported in other intercalated fullerides. 18,[38][39][40] From another point of view the covalent 3D network in such C 60 polymers, containing carbon cages, can be seen as carbon analogs of silicon clathrate compounds. Recently, the barium-containing silicon clathrate compound Ba 8 Si 46 , isotypic with the type-I gas (G) hydrate Gx-(H 2 O) 46 , has been proved to be a superconductor with a transition temperature (T c ) of 8.0 K. 41 It could, therefore, be speculated that the 3D Na 4 C 60 phase observed in our experiments might possess a structure similar to that of such compounds but composed of carbon instead of silicon.…”
Section: Discussionmentioning
confidence: 99%
“…Third, a key feature for obtaining a ferromagnetic phase is mutual orientation of adjacent fullerene molecules [14]. Similar situation occurs with fullerene-based solids having an antiferromagnetic ground state: the sign of magnetic interactions between C 60 anions depends on the relative orientation of neighboring molecules [15].…”
Section: Role Of Orientational Orderingmentioning
confidence: 94%
“…[7][8][9] There are also doped fullerides that display ferromagnetism, antiferromagnetism, and giant magnetoresistance. [10][11][12] At the molecular level, a recent experiment by Yamachika et al has shown that a single C 60 molecule can be doped with individual potassium atoms. 13 In the experiment K atoms adsorbed on the Ag ͑001͒ surface can be attached to an isolated C 60 molecule by moving the molecule over them using a scanning tunneling microscope tip.…”
Section: Doping a C 60 Molecule With Potassium Atoms: A Theoretical Smentioning
confidence: 99%